A phase I trial of inotuzumab ozogamicin in combination with temsirolimus in patients with relapsed or refractory CD22-positive B-cell non-Hodgkin lymphomas. Issue 1 (2nd January 2022) - Pirosa, Maria C.; Zhang, Lu; Hitz, Felicitas; Novak, Urban; Hess, Dagmar; Terrot, Tatiana; Pascale, Mariarosa; Mazzucchelli, Luca; Bertoni, Francesco; Cavalli, Franco; Zucca, Emanuele; Stathis, Anastasios
Abstract: This phase I trial evaluated the safety, tolerability, and preliminary activity of inotuzumab ozogamicin in combination with temsirolimus in patients with relapsed/refractory CD22 positive B-cell non-Hodgkin lymphomas. Nineteen patients received at least one dose of both study drugs. Dose-limiting toxicities consisted of thrombocytopenia, hypertriglyceridemia, oral mucositis, clinical deterioration, and the inability to receive at least three doses of temsirolimus during cycle 1. The most common grade ≥3 treatment-related adverse events were thrombocytopenia ( n  = 8), neutropenia ( n  = 5), and two patients each hyperphosphatemia, lymphopenia, and hypertriglyceridemia. The recommended phase II dose was inotuzumab ozogamicin 0.8 mg/m 2 on day 1 in combination with temsirolimus 10 mg on days 8, 15, and 22 every 28 days. Among 18 patients evaluable, seven (39%) with follicular lymphoma had a partial remission. This drug combination is not possible within a therapeutically useful range of doses due to toxicities. Antitumor activity was observed in heavily pretreated patients (ClinicalTrials.gov, Identifier NCT01535989).